Randomized pilot trial comparing tolvaptan with furosemide on renal and neurohumoral effects in acute heart failure. (31st March 2016) - Jujo, Kentaro; Saito, Katsumi; Ishida, Issei; Furuki, Yuho; Kim, Ahsung; Suzuki, Yuki; Sekiguchi, Haruki; Yamaguchi, Junichi; Ogawa, Hiroshi; Hagiwara, Nobuhisa
Abstract: Aims: Loop diuretics are first‐line medications for congestive heart failure (CHF); however, they are associated with serious adverse effects, including decreased renal function, and sympathetic nervous and renin–angiotensin system activation. We tested whether tolvaptan, a vasopressin V2‐receptor antagonist, could reduce unfavourable furosemide‐induced effects during CHF treatment. Methods and results: Sixty patients emergently hospitalized owing to CHF‐induced dyspnea were randomly assigned to receive either 40 mg intravenous furosemide daily or 7.5 mg oral tolvaptan for 5 days after admission. Both groups also received intravenous carperitide and canrenoate potassium. As results, baseline patient characteristics were similar between the furosemide ( n  = 30) and the tolvaptan ( n  = 30) groups, with no significant difference in 5 day urine volume or fluid balance. Brain natriuretic peptide and body weight improvements were similar between groups. However, serum creatinine (Cr) level did not increase, and the incidence of worsening renal function was significantly lower in the tolvaptan group. Consequently, the Cr increase to gain 1000 mL urine was 2.5‐fold lower in the tolvaptan group. Furthermore, the blood urea nitrogen (BUN)/Cr ratio significantly decreased in the tolvaptan group, suggesting that renal perfusion was preserved, and urea reuptake and passive water reabsorption were suppressed following tolvaptan treatment. Although catecholamine improvements after treatment were not significantly different, plasma renin activity was enhanced in the furosemide group. Conclusions: As compared with furosemide, tolvaptan in patients with acute heart failure is associated with comparable decongestion, better preservation of renal function and less activation of renin–angiotensin system. (UMIN 000014134).